UZBEK PRIMARY SCHOOL STUDENTS` REACTION TOWARDS THE USE OF CLIL METHODOLOGY IN ART CLASSES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The current paper is aimed at the determination of primary school students` attitudes towards the use of CLIL methodology and is a part of longitudinal research oriented on the effectiveness of CLIL methodology in Uzbek primary schools. Previously, there has been done research to study the school teachers` views on the implementation of Content and Language Integrated Learning (CLIL) methodology in primary schools of Uzbekistan. The research results were not strong enough to decide whether to teach content and language in integration or not. Some teachers showed a strong disagreement with the idea, whereas the others were interested in the new approach to teaching the language (however, they were also not sure how well it might succeed in Uzbek schools). Therefore, the current research was done with the purpose to identify the primary schoolers` attitudes towards CLIL classes. The research is not about the effectiveness of the method yet, it will only focus on the reaction of primary school students to the subject being taught through the second language.